2021
DOI: 10.7759/cureus.18580
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report of Acute Transient Encephalopathy Following a Trans-esophageal Echocardiography

Abstract: Methemoglobinemia is caused due to an increase in methemoglobin in the blood, impairing oxygen transfer to tissues. Acquired methemoglobinemia is caused by various drugs like local anesthetics, antibiotics, nitrates, nitrites, and food additives. We present a case of a 73-year-old male who presented with cyanosis, altered mental status, and hypoxia following transesophageal echocardiography. Arterial blood gas analysis revealed methemoglobinemia. He had been given topical lidocaine and benzocaine spray before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…[ 10 ] presented a case of methemoglobinemia and acute hemolysis induced by tetracaine lozenges. Several studies reported methemoglobinemia induced by inhalation of anesthetics [ 11 , 12 ]. Methemoglobinemia is diagnosed by pulse oximetry, patient symptoms, and ABG with CO-oximetry [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 ] presented a case of methemoglobinemia and acute hemolysis induced by tetracaine lozenges. Several studies reported methemoglobinemia induced by inhalation of anesthetics [ 11 , 12 ]. Methemoglobinemia is diagnosed by pulse oximetry, patient symptoms, and ABG with CO-oximetry [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the cases presented, diagnosis of sodium nitrite toxicity was based on a wide variety of information obtained from the decedent history, death scene, autopsy, toxicology, and biochemistry findings, often in the absence of a definitive, quantitative diagnostic test. While there are several other possible causes of methemoglobinemia, both congenital and acquired (including recessive congenital methemoglobinemia [43], mothball intoxication [44] and dapsone overdose [45], and several other substances [46]), all death investigations demonstrated evidence of sodium nitrite ingestion. Furthermore, use of the urinalysis dipstick for presumptive nitrite detection was applied in the latter eight cases, which all returned a positive result, raising suspicion of potential sodium nitrite toxicity and prompted further investigations.…”
Section: Discussionmentioning
confidence: 99%